Blurred borders. Negotiating Copresence in the Family Home Through Spatio-Temporal Strategies for Increased Adult Well-Being - Costa Santos, Sandra; Parnell, Rosie; Abo Kanon, Husam; Pattinson, Emily; Pitsikali, Alkistis; Sarhan, Heba (Home cultures, 2024)
Borders between the domestic domains of work, family and restoration, are essential to adult well-being. This article interrogates the blurring of these borders by post-pandemic, reshaped relations between adults and children in domestic space. Adult spaces can alleviate the negative well-being effects of blurred borders, but inadequate consideration of intrafamilial separation in contemporary housing forces parents to negotiate adult-child copresence, or 'presence to one another.' Drawing on time-geography, this article explores adult spaces of avoidance in the family home to negotiate negative copresence and maintain domestic borders. Qualitative analysis of 45 in-depth interviews shows adults in England and Scotland (UK) enacting spatio-temporal tactics -appropriation, exclusion, exile and containment- to negotiate negatively perceived copresence and alleviate its detrimental well-being impacts. Understood as a key component of togetherness, the article demonstrates the relationship between copresence and the physical space of the house, highlighting implications of negatively perceived copresence for housing design.